Health and Civil War in Rural Burundi : Health and Civil War in Rural Burundi - Bundervoet, Tom (World Bank, Washington, DC, 2012)
This paper combines household survey data with event data on the timing and location of armed conflicts to examine the impact of Burundi's civil war on children's health status. The identification strategy exploits exogenous variation in the war's timing across provinces and the exposure of children's birth cohorts to the fighting. After controlling for province of residence, birth cohort, individual and household characteristics, and province-specific time trends, the authors find that children exposed to the war have on average 0.515 standard deviations lower height-for-age z-scores than non-exposed children. This negative effect is robust to specifications exploiting alternative sources of exogenous variation.